Mejoramiento genético y actividades relacionadas. Actividades relacionadas. América Central y el Caribe - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
In 1986 the bean program for Central America and the Caribbean, including tropical Mexico and Panama, continued with the transfer of technology generated by the national programs to the farmers, through efficient on-farm research. An efficient network of information and material on beans was formed, and was furthered by active exchange between the countries. Courses offered by the various countries were oriented towards the training of on-farm researchers to ease technology transfer between national programs and farmers. Research for the incorporation of resistance to BGMV, Apion, slugs, web blight, and common bacterial blight was continued. Results are included. (CIAT)